Developing a Walking Exercise Program for Women in Menopause Transition and Testing Outcome Measures (poster). (December 2017) - Ross, Sue; Sydora, Beate; Davenport, Margie; Yuksel, Nese; Shandro, Tami
Abstract : Background: Walking is a simple, low cost, and widely accessible activity with proven health benefits. We plan to study the impact of walking therapy on sleep and quality of life (QOL) for women who are adversely affected by menopausal symptoms. The objective of this present study is to undertake preliminary work essential for the design of a rigorous study. Aims: We plan a series of linked pilot projects: (1) A systematic review of the published literature to investigate characteristics of therapeutic walking programs for women in menopause transition. (2) An environmental scan of walking areas and programs available in the Edmonton area that would provide year-round, engaging walking opportunities for women.(3) Focus groups to identify features of walking programs that women perceive as attractive.(4) Accelerometers use to establishing whether accelerometers provide an adequate method to measure activity and sleep disturbance outcomes. Methods: The four pilot projects will use complementary methods: Aim 1: In collaboration with a librarian, we will conduct a systematic review of published therapeutic walking programs for menopausal women to identify features (adherence by women, health improvements) that have produced successful outcomes; Aim 2: We will explore and gather information on walking programs and areas to determine their appeal to menopausal women with regard to neighborhood characteristics, easy walkability, attractive natural or business surroundings; Aim 3: A minimum of three focus groups with each 6-8 women recruited from Edmonton Menopause clinics will be held to find out what features of walking would encourage (or discourage) them to join and persist with a therapeutic walking group; Aim 4: Women from the focus groups will be invited to wear accelerometers for 7 days to test if they provide an acceptable method to measure activity and sleep disturbance. Value of the Research: Results from this preliminary work will be used to further the long-term goal of designing a rigorous trial to study the effect of a walking program on menopause and sleep-related QOL (measured using standardized QOL questionnaires) in Northern cities. Our ultimate goal is to produce evidence to provide wellness options for women in menopause transition and post-menopause.